2016
DOI: 10.1038/srep30421
|View full text |Cite
|
Sign up to set email alerts
|

Human Trefoil Factor 3 induces the transcription of its own promoter through STAT3

Abstract: Human trefoil factor 3 (hTFF3) is a small peptide of potential therapeutic value. The mechanisms underlying the transcriptional regulation of hTFF3 remain unclear. The purpose of this study was to identify the core functional elements for the self-induction action of hTFF3 and transcription factors. First, truncated promoters were constructed to identify the functional regions of the hTFF3 promoter. Next, point mutation, chromatin immunoprecipitation, RNA interference, and gene overexpression experiments were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…The regulatory cross-talk among the three Trefoil peptides was already described (Taupin et al, 1999 ), nevertheless our analysis highlights such crosstalk upon Helicobacter infection. Interestingly, in hyper-expressing clone TFF1 is so strongly induced that its level cannot be explained as the mere sum of dox-induced plus H. pylori- induced mRNA; such result could be justified with an auto-induction mechanism, already described for TFF2 and TFF3 (Bulitta et al, 2002 ; Sun et al, 2016 ), and we are currently examining this possibility.…”
Section: Discussionmentioning
confidence: 71%
“…The regulatory cross-talk among the three Trefoil peptides was already described (Taupin et al, 1999 ), nevertheless our analysis highlights such crosstalk upon Helicobacter infection. Interestingly, in hyper-expressing clone TFF1 is so strongly induced that its level cannot be explained as the mere sum of dox-induced plus H. pylori- induced mRNA; such result could be justified with an auto-induction mechanism, already described for TFF2 and TFF3 (Bulitta et al, 2002 ; Sun et al, 2016 ), and we are currently examining this possibility.…”
Section: Discussionmentioning
confidence: 71%
“…Trefoil factor 3 (TFF3) is a small peptide that has essential roles in restitution, such as cell migration to heal superficial lesions, and in regeneration, including differentiation and proliferation in the repair of the epithelia. [1][2][3] It has been suggested that TFF3 is expressed in all mucus-secreting tissues, including the renal tubules. 4 The TFF3 expression increases in various organs as the consequence of tissue damage such as inflammation or fibrosis.…”
Section: Methodsmentioning
confidence: 99%
“…TFF3-mediated cytoprotective functions are well-documented and are associated with activation of EGFR and ERK in various cell lines derived from pancreas, lung, and colon 3,24,25 26 . While TFF3 can regulate the transcription factor STAT3 by promoting Stat3 phosphorylation and STAT3 transcriptional activation of TFF3 and other STAT3-dependent genes 27,28 , these effects are not mediated by direct binding of TFF3 to the EGFR 29 . To determine if TFF3 instead impacts EGFR signaling and subsequent STAT3-dependent signaling through LINGO2, we used a murine intestinal adenocarcinoma cell line (MC38) that expresses all four LINGO family member genes, with LINGO2 showing highest expression ( Figure 2A).…”
Section: Discussionmentioning
confidence: 99%